Analysis of Educational Unit Curriculum Documents and Their Implications in Supporting Deep Learning and Local Cultural Integration in Elementary Schools with the CIPP Model - Trijoko Bagus Setyawan; Azhariyanti Mei Ghita (Jurnal Inovasi dan Riset Pendidikan Dasar, 2026)
This study aims to analyze the Education Unit Curriculum (KSP) document and its implications for supporting in-depth learning and local cultural integration in elementary schools using the CIPP evaluative model. This study employed a qualitative approach with document analysis of the KSP, learning tools, and school curriculum analysis instruments. Data analysis was conducted based on the four CIPP components: context, input, process, and product. The results indicate that the KSP document aligns with national education goals and supports the implementation of in-depth learning through active, reflective, and contextual learning strategies. The integration of local culture is reflected in the school vision, local content, and environment-based learning activities. However, limitations remain in character assessment planning, consistency of learning implementation, and availability of supporting facilities. This study concludes that the KSP plays a strategic role as a foundation for in-depth learning and strengthening local culture, necessitating improvements in planning quality, strengthening teacher competencies, and ongoing evaluation.